2014
DOI: 10.4244/eijv10i5a97
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention for coronary bifurcation disease: consensus from the first 10 years of the European Bifurcation Club meetings

Abstract: The European Bifurcation Club (EBC) is an independent, non-political and informal "think tank" of scientists with a particular interest in clinical, technical and fundamental aspects of the management of coronary artery bifurcation disease. Bifurcations account for 15-20% of all percutaneous coronary interventions (PCI) and remain one of the most challenging lesions in interventional cardiology in terms of procedural success rate as well as long-term cardiac events. The optimal management is, despite a fast gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
204
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(214 citation statements)
references
References 100 publications
5
204
0
5
Order By: Relevance
“…These results reflect the earlier results with SB flow-guided strategy, performed with a first-generation DES (with a difference of more than doubled restenosis rates at shorter follow-up time) [46]. Some authors are against SB predilatation considering the potential for major dissection of the SB ostium, requiring additional stenting (which is also the official position of the European Bifurcation Club) [2]. However, the randomised study comparing predilatation with no-predilatation before main vessel stenting demonstrated improved TIMI flow after MB stenting and less indication to subsequently treat the SB [47].…”
Section: Side-branch Compromise and Periprocedural Myonecrosis: How Msupporting
confidence: 72%
See 4 more Smart Citations
“…These results reflect the earlier results with SB flow-guided strategy, performed with a first-generation DES (with a difference of more than doubled restenosis rates at shorter follow-up time) [46]. Some authors are against SB predilatation considering the potential for major dissection of the SB ostium, requiring additional stenting (which is also the official position of the European Bifurcation Club) [2]. However, the randomised study comparing predilatation with no-predilatation before main vessel stenting demonstrated improved TIMI flow after MB stenting and less indication to subsequently treat the SB [47].…”
Section: Side-branch Compromise and Periprocedural Myonecrosis: How Msupporting
confidence: 72%
“…These results are comparable with results from other studies shown in the Table 1. The most important asset of this analysis is the large number of patients constituting a homogenous group treated systematically with provisional T-stenting, currently the most recommended strategy [2]. These results from Germany are in accordance with the pooled analysis of coronary bifurcation patients treated with a first-and second-generation DES [25].…”
Section: What Do the Data Currently Demonstrate About Bifurcationsupporting
confidence: 71%
See 3 more Smart Citations